The Temporal Dynamics of Visual Processing in Multiple Sclerosis - Costa, Silvana Lopes (2015)
Although the integrity of the visual system is often affected in multiple sclerosis (MS), the potential relationship between the temporal dynamics of visual processing and performance on neuropsychological tests assessing processing speed (PS) remains relatively unexplored. Here, we test if a PS deficit is related to abnormalities within the visual system, rather than impaired higher-level cognitive function. Two groups of participants with MS (1 group with PS deficits and another without) and a healthy control group, matched for age and education, were included. To explore the temporal dynamics of visual processing, we used 2 psychophysical paradigms: attention enhancement/prioritization and rapid serial visual presentation. Visual PS deficits were associated with a decreased capability to detect visual stimuli and a higher limitation in visual temporal-processing capacity. These results suggest that a latent sensorial temporal limitation of the visual system is significantly associated to PS deficits in MS.